O funkcjach urojenia okoliczności wyłączających bezprawność. Wybrane zagadnienia teoretycznoprawne - Tarapata, Szymon; Zakrzewski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
It has been established in this paper that delusion as to the circumstances excluding unlawfulness has three different functions in the structure of criminal liability premises. Firstly, it may exclude unlawfulness, which takes place in a situation where a perpetrator had no chance to realise that in reality the objective elements of unlawfulness exclusion had become real. Secondly, if the perpetrator erroneously stated that he was acting under the exclusion of unlawfulness while it was only objectively but not subjectively recognisable that it was not so, the perpetrator’s criminal liability would be excluded due to lack of fault. Thirdly and finally, if the perpetrator deluded that he was acting under the exclusion of unlawfulness while it was objectively and subjectively recognisable that it was not so, then all the requirements of the criminality of the act are met and the act of the perpetrator is to be found unlawful and culpable.
Keywords: okoliczności wyłączające bezprawność; wyznaczenie podmiotu; opis czynu zabronionego